A Critical Review of Schmertmann’s Strain Influence Factor Method for Immediate Settlement Analysis - Pantelidis, Lysandros (My University, 2020)
This paper offers an in-depth review of Schmertmann’s strain influence factor method for immediate settlement analysis. The method in question is among the most popular worldwide, whilst, it is included in various important design codes worldwide (e.g. Eurocode 7, FHWA NHI-06-089). As shown, Schmertmann’s method has been proposed without proper and adequate documentation, whilst it presents serious weaknesses related to its calibration and the values adopted for various factors used. In addition, comparison between measured and calculated settlement values of structures or full-size test footings (data taken from independent studies) indicates that Schmertmann’s method is a poor prediction tool. In this respect, an integrated index is suggested for the quantification of the “effectiveness” of the various settlement analysis methods (including the Schmertmann’s one). This consists of the mean and the coefficient of variation of the calculated over the measured settlement ratio values and the percentage of the cases for which the calculated settlement results greater than or equal to the measured settlement. The very low “effectiveness” index values obtained gave rise to investigating the possible sources of error. A parametric finite element analysis was, finally, carried out for supporting the main findings.
Keywords: Schmertmann’s method; Strain influence factor; Immediate settlement analysis; Elastic settlements; Shallow foundations